(untitled) (Global Journal of Human-Social Science, 2024)
Oblivion that saves dramatic representation in the backstage of Christian publicity ritual matrices in local communities of beings human and non-human reverse hospitality in those experiences and expressions there are other very other ethics other politics other epistemic ways of knowledge Following their paths I have talked and written thinking with in on my feet about semiopraxis An extended common disciplinary and social sense perceives and thinks Culture as a way of seeing feeling and living within a community that gathers around this pregnating consensus But this is a Westernized way of understanding culture marked by Eurocentric defensive selftropings and its policies of world colonization In outer non-Western communities the sense the practices and above all the medium of hospitality is other Grosso 2014a 2015a 2017a The concept of community expands there and embraces human beings together with the nonhuman the living and the dead gods and elements in a network of relationships